Pengaruh Penggunaan Tepung Roti Kadaluarsa dan Tepung Keong Mas dalam Ransum Burung Puyuh terhadap Konsumsi Energi, Konsumsi Serat Kasar dan Konsumsi Air Minum: Ransum puyuh - Dara Surtina; Harissatria; Kiki Despio (Program Studi peternakan, 2022)
This study aims to determine the effect of using expired bread flour and golden snail flour in quail rations on energy consumption, crude fiber consumption and drinking water consumption. The livestock used were female quails aged 14 weeks (egg laying period) totaling 80 tails. Bread comes from the bakery PT. Nagari Minang Jelita is located on Jl. Cross Sumatra KM.13 Jorong Kubang Nagari Singkarak Kab. solo. The design of this study was a completely randomized design (CRD) which consisted of 4 treatments, namely: P0 (given yellow corn without TRK and TKM), P1 (10% TRK and 5.35% TKM), P2 (20% TRK and 10 ,65% TKM), P3 (30% TKM and 16% TKM). Each treatment consisted of 5 cage units as replicates. Each cage unit is filled with 5 quails. The variables measured in this study were energy consumption, crude fiber consumption and drinking water consumption. The results showed that the average energy consumption was P0=58,69; P1=58,29; P2=59,41; P3=61,38 Mcal/head/day, crude fiber consumption is P0=0,80; P1=0,80; P2=0,81; P3=0,82 gram/head/day and drinking water consumption is P0=66,11; P1=64,81; P2=64,11; P3=65,41 ml/head/day. The results of the study concluded that the effect of giving expired bread flour and golden snail flour in the ration had a non-significantly different effect (P>0.05) on energy consumption, crude fiber consumption and quail drinking water consumption.